Effects of paranephric blockade in the management of nephritis in buffaloes - SHARDA, RAJU; KUMAR, AMRESH; JADON, N S (The Indian Journal of Animal Sciences, 2014)
Paranephric blockade with 0.5% solution of lignocaine hydrochloride along with parenteral enrofloxacin (floxidin) in experimental nephritis in buffalo calves showed an early recovery as compared to the treatment with lignocaine hydrochloride and enrofloxacin alone. The physiological parameters (heart rate, respiratory rate and temperature) returned to near normal level by day 10 and haematological parameters (total leucocyte count, differential leucocyte count, haemoglobin and packed-cell volume) by day 13 in animals given paranephric block alongwith antibiotics as compared to day 16 and 21 in antibiotic and paranephric block alone administered animals. Various biochemical parameters (creatinine, blood urea nitrogen, glucose total protein, albumin, calcium, phosphorus, urinary alkaline phosphatase and gamma glutamyl transferase)returned to base level by day 16 in animals given paranephric block along with antibiotics as compared to day 21 in paranephric block and antibiotic alone administered animals.